A novel dual-additive strategy for cleaner diesel combustion: The combined effects of diethyl carbonate and limonene on energy conversion, combustion dynamics, and emission behavior - Sevinc, Huseyin (Elsevier, 2026)
This experimental study investigates how dual-additive fuel blending affects combustion, thermal response, performance, and emissions in a small-scale diesel engine. Diethyl carbonate (DEC) and bio-derived limonene were used as oxygenated and renewable additives, and four fuels (D100, D90DEC10, D90LM10, and D90DEC5LM5) were tested in a single-cylinder diesel engine at 2000 rpm under loads of 1-3 kW. Combustion and thermal analyses included in-cylinder pressure, heat release rate (HRR), combustion duration, vibration, noise, exhaust gas temperature (EGT), and infrared thermography. Among the tested fuels, D90LM10 exhibited the most pronounced premixed combustion behavior and delivered the best overall performance, with an average 15.9% reduction in brake specific fuel consumption (BSFC), an 18.5% increase in brake thermal efficiency (BTE), a 48.4% decrease in CO emissions, up to a 23% reduction in HC emissions, and nearly a 70% reduction in smoke opacity relative to neat diesel. In contrast, D90DEC10 moderated pressure rise and heat-release intensity, yielding the lowest average vibration amplitude (4.4% lower than diesel), a 32.6% reduction in smoke emissions, and a moderate 4-5% decrease in NOX. The dual-additive blend D90DEC5LM5 provided a balanced response, with 6.3% lower BSFC, 9.2% higher BTE, 26.5% lower CO emissions, and 40-45% lower smoke opacity than diesel. Thermographic analysis at full load showed surface temperature reductions of 4.3%, 10.7%, and 6.5% for D90DEC10, D90LM10, and D90DEC5LM5, respectively. Overall, DEC-limonene blending offers an effective route for improving diesel-engine efficiency while reducing vibration, thermal stress, and major exhaust pollutants.
Keywords: Diesel engine; Limonene; Diethyl carbonate; Combustion; Fuel additives; Exhaust emissions